Archaeological Protein Residues: New Data for Conservation Science - Andrew Barker (Ethnobiology Letters, 2011)
The utility of zooarchaeological data for addressing wildlife management and conservation research has been increasingly recognized over the past two decades. As the field of ‘applied zooarchaeology’ continues to grow, newfound opportunities for discovery have arisen via collaborative interdisciplinary approaches. The burgeoning field of proteomics, in particular, has provided numerous opportunities for enhancing the degree to which meaningful information can be recovered from the archaeological record. Archaeological protein residues can inform conservation biologists about paleobiogeography and ecological/evolutionary history and thereby provide insight into wildlife management strategies. In addition to pointing out several cases where archaeological protein residues may be of benefit, I justify the use of protein residues in particular and discuss areas for improvement.